The Construction of Middle School Chemistry Efficient Classrooms Under the Background of New Curriculum Reform in China - Gao, Yuan; Xu, Suyi; Xu, Ying (Advances in Social Sciences Research Journal, 2022)
From 1949 to the present, China’s basic education has undergone eight curriculum reforms. The “Outline of China’s Education Reform and Development ”issued in June 1994 clearly put forward the concept of quality education, and "quality education" has become the main theme of curriculum reform. In 2022, a new round of curriculum reform vigorously implemented the policy of "core literacy" and comprehensively cultivating high-quality talents. Quality education and high-efficiency classroom teaching research to comprehensively promote core literacy education have been paid more and more attention by the majority of researchers. The revised two-dimensional framework of the theory of Bloom’s classification of educational objectives is helpful to build an efficient classroom and cultivate students’ high-level thinking. In combination with the teaching practice under the background of basic education reform, this study discusses the construction methods and strategies of high-efficiency chemistry classroom in Middle School under the theory of Bloom’s classification of educational objectives.